2021
DOI: 10.1097/pai.0000000000000903
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Immune Checkpoint Regulators, Cytotoxic T-Lymphocyte Antigen-4, and Programmed Death-Ligand 1 in Epstein-Barr Virus-associated Nasopharyngeal Carcinoma

Abstract: Background: Nasopharyngeal carcinoma (NPC) is the most common cancer arising from the nasopharynx with a poor prognosis. Targeting immune checkpoint is one of the new promising lines in cancer treatment. Cytotoxic T-lymphocyte antigen-4 (CTLA-4) and programmed death-ligand 1 (PD-L1) are immune checkpoints that regulate T-cell immune function.Aim: This work aimed to assess the immunohistochemical expression of PD-L1 and CTLA-4 in NPC and their ability to predict survival and response therapy and to check their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…Therefore, PD-L1 may be an effective target for immunotherapy as well as a useful biomarker for predicting metastasis and survival. Many studies have investigated the role of PD-L1 expression and EBV in the prognosis and risk stratification of NPC, as well as other EBV-associated malignancies, but most of them did not combine tumor PD-L1 expression with EBV-DNA to further stratify NPC patients ( 30 , 33 , 47 51 ) Hu and colleagues stratified NPC patients into three groups based on the combination of EBV DNA load and PD-L1 expression on tumor infiltrating lymphocytes (TILs). The results indicated that a high log EBV-DNA load with low TIL PD-L1 was a poor prognostic factor for PFS ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, PD-L1 may be an effective target for immunotherapy as well as a useful biomarker for predicting metastasis and survival. Many studies have investigated the role of PD-L1 expression and EBV in the prognosis and risk stratification of NPC, as well as other EBV-associated malignancies, but most of them did not combine tumor PD-L1 expression with EBV-DNA to further stratify NPC patients ( 30 , 33 , 47 51 ) Hu and colleagues stratified NPC patients into three groups based on the combination of EBV DNA load and PD-L1 expression on tumor infiltrating lymphocytes (TILs). The results indicated that a high log EBV-DNA load with low TIL PD-L1 was a poor prognostic factor for PFS ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Using IGg antibody against CD133 (CD133/Prominin-1 (PROM1) Concentrated, Code: RM0202, Clone: MD49R, Source: Rabbit, The EnVision TM FLEX + system (DAKO, North America Inc, CA, USA) was used for immunohistochemical staining, which was a two-step polymer-enhanced IHC detection method. Recommended 3in-1 specimen preparation procedure using pretreatment procedure: Deparaffinization, rehydration, and heat-induced epitope recovery were performed in paraffin-embedded tissue sections (7,8) . The staining steps with the recommended incubation time were reprogrammed in the Auto Stainer Link 48 software.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Representative samples from all specimens were immunohistochemically stained with the PAX8, CK7, p16, p53, HNF-1B and, Napsin A antibodies. The immunohistochemistry technique was performed as fellow; initially, heating was used to extract antigens from tissue sections (16)(17)(18) . The sections were treated and chilled overnight with PAX8, CK7, p16, p53, HNF-1B and Napsin A rabbit monoclonal primary antibodies.…”
Section: Histopathological Studymentioning
confidence: 99%